The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0103-97332006000100007
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of biplanar gradient coils for magnetic resonance imaging

Abstract: "Open" magnetic resonance imaging (MRI) scanners are frequently based on electromagnets or permanent magnets, and require self-shielded planar gradient coils to prevent image artifacts resulting from eddy currents in metallic parts of the scanner. This work presents an optimization method for the development of self-shielded gradient coils with biplanar geometry for "Open" MRI scanners. Compared to other optimization methods, this simple approach results in coils that produce larger uniform gradient volumes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Planar gradient coils provide an interest to researchers due to their ability to be separated and also because the DSV contained between the plates is more accessible (87)(88)(89)(90)(91)(92)(93)(94)(95)(96). The DSV is the region in which a quality image can be obtained and it should be as large as possible for a given plate size.…”
Section: Planar Gradient Coilsmentioning
confidence: 99%
“…Planar gradient coils provide an interest to researchers due to their ability to be separated and also because the DSV contained between the plates is more accessible (87)(88)(89)(90)(91)(92)(93)(94)(95)(96). The DSV is the region in which a quality image can be obtained and it should be as large as possible for a given plate size.…”
Section: Planar Gradient Coilsmentioning
confidence: 99%
“…To this end, it can be shown that for a 3D Gaussian function the variance must scale by the inverse cube-root of the amplitude (see [46]). Applying the Gaussian filter (22) to the density map (20) produces an updated density map and the next streamline is seeded at the location corresponding to the maximum of this new density map. The entire process is repeated continuously, whereby the density map is successively lowered with each additional streamline, until the maximum of the updated density map falls below some threshold.…”
Section: Obtaining 3d Coil Windings and Calculating Coil Performancementioning
confidence: 99%
“…Additionally, coils of finite extent may be obtained by considering, for example, Fourier series representation for the current density [16][17][18][19]. Alternatively, it is also possible to design both cylindrical and biplanar gradient coil sets using coil-space optimisation strategies such as simulated annealing (see for example, [20][21][22]). …”
Section: Introductionmentioning
confidence: 99%
“…In planar gradient coil geometry, the y ‐gradient has two fingerprint winding patterns along the z ‐axis with current flowing clockwise on one loop and counterclockwise on the other loop. Unlike cylindrical gradient coils where the x ‐gradient pattern can be obtained with a 90° rotation of the y ‐gradient, the x ‐gradient for planar gradient coils is achieved with windings that are laid out as a 2 × 2 fingerprint pattern on each plane with current flowing clockwise and counterclockwise alternatively (10–20).…”
Section: Theorymentioning
confidence: 99%